Morphological characteristics of microenvironment in the human thymus during fetal development - Nemanja Maletin; Nikola Denda; Stefan Borocki; Zoran Golušin; Aleksandar Rašković; Aleksandra Fejsa-Levakov; Bojana Andrejić Višnjić; Jelena Amidžić (BMC Research Notes)
Abstract Background The thymus is a key organ for the development of T cells. T cell precursors first migrate from the bone marrow to the thymus. During maturation, these precursors require interactions with various types of cells that form the thymic microenvironment, such as epithelial, mesenchymal, and other immune cells not belonging to the T lineage. The aim of this study was to examine the changes in the number and diameter of Hassall’s corpuscles, as well as the density and distribution of epithelial cells (p63+) and macrophages (CD68+). Methods Twenty-five fetal thymus samples were examined, divided into five groups according to gestational age. The samples were processed using standard histological methods and immunohistochemical staining. Results The study showed that the number and diameter of Hassall’s corpuscles gradually increased during fetal development, with a significant increase from the 14th to the 38th gestational week. The average diameter of Hassall’s corpuscles was largest in the age group of 34–38 weeks. The density of p63 + epithelial cells decreased in correlation with gestational week, while the density of CD68 + macrophages significantly increased, particularly in the thymic medulla, towards the end of the fetal period. Conclusions An increase in the number and size of Hassall’s corpuscles during fetal development was recorded, while the density of epithelial cells decreased and the density of macrophages increased.